Prevention of malaria in pregnancy: The threat of sulfadoxine-pyrimethamine resistance - Sundararaman, Sesh A.; Odom John, Audrey R. (Frontiers in Pediatrics, 2022)
Malaria infection in pregnancy can lead to adverse outcomes for both the pregnant person and fetus. The administration of intermittent preventative therapy (IPTp) with sulfadoxine-pyrimethamine (SP) during pregnancy (IPTp-SP) improves outcomes, including severe maternal anemia, placental malaria infection, and low infant birth weight. The WHO recommends IPTp-SP for pregnant individuals living in areas of moderate or high malaria transmission in Africa. The current regimen consists of two or more doses of SP starting as early as possible in the second trimester, at least one month apart. Unfortunately, rising Plasmodium falciparum SP resistance throughout Africa threatens to erode the benefits of SP. Recent studies have shown a decrease in IPTp-SP efficacy in areas with high SP resistance. Thus, there is an urgent need to identify new drug regimens that can be used for intermittent preventative therapy in pregnancy. In this review, we discuss recent data on P. falciparum SP resistance in Africa, the effect of resistance on IPTp-SP, and studies of alternative IPTp regimens. Finally, we present a framework for the ideal pharmacokinetic and pharmacodynamic properties for future IPTp regimens.